QIP on baseline prolactin monitoring in psychiatric inpatients on antipsychotics. Issue 5 (September 2015) - Ali, Shaazneen; Thomas, Emily Simon; Looby, Saran; Beveridge, Ed
<x xml:space="preserve">Abstract</x> Mental health patients suffer higher rates of mortality and morbidity due to physical health problems. A number of antipsychotics are associated with significant increases in plasma prolactin levels and the risk of hyperprolactinaemia. The importance of physical health monitoring is increasingly recognised and commissioned for in mental health services. In the context of greater focus on physical health monitoring in mental health settings, this project set out to assess and improve compliance with guidance on baseline prolactin level testing of inpatients on antipsychotics.